Organizational Dynamics of Islamic Education Institutions - Khuseini, Ahmad; Abidin, Zainal; Warisno, Andi; Andari, An An; Anshori, M Afif (Graduate Program Magister Manajemen Pendidikan, 2023)
In this library research, we discuss 1) What is the birth background and history of Mathlaul Anwar’s Social Religious and Educational Organization? 2) The role of Mathlaul Anwar in the field of education and social religion; 3) What are the future challenges for Mathlaul Anwar in realizing the Socio-Religious and Educational Vision? The result found the birth and history of Mathlaul Anwar’s social religious and educational organization was to respond to the conditions of Banten at that time. The role of Mathlaul Anwar in the field of education and social religion. The future challenge for Mathlaul Anwar in realizing his socio-religious and educational vision is Mathlaul Anwar’s temptation from practical politics and extracting financial resources for the organization.